A comparative study to evaluate the Q3 characteristics of different tretinoin microspheres available in the Indian market to the innovator or the reference listed drugs - Chinda, Monika; Patro, K. Balakrishna; Qureshi, Ravish; Langde, Amol; Kukreja, Anil; Patel, Hiren (International Journal of Research in Dermatology, 2025)
Background: With the increasing availability of tretinoin microsphere gels in the Indian pharmaceutical market, comparative evaluation against market products and the U.S. reference listed drug (RLD) becomes essential to assess quality, safety, and performance consistency. Methods: This study presents a comprehensive Q3 characterization a test product with 0.04% marketed by Emcutix in comparison with the U.S. RLD, retin-A micro gel, and various Indian marketed tretinoin gel brands A, B, and C (0.04% tretinoin). The evaluation focused on key physicochemical and structural attributes including appearance, texture, pH, drug content, viscosity, specific gravity, phase morphology, and in vitro release testing (IVRT). Results: The test product 0.04% exhibited visual appearance, texture, pH, and tretinoin content similar to RLD. In contrast, the marketed products demonstrated deviations in appearance and suboptimal drug content, failing to meet USP and BP overage allowances. Viscosity (38,000 cPs) and specific gravity (1.047) of the test product 0.04% were within acceptable ranges, closely matching the RLD values. Microsphere morphology revealed well-formed, spheroidal particles in test product 0.04% and brand A formulation, while brand C and Brand B lacked such microsphere structures. IVRT profiles showed that the test product and brand A formulation showed the slowest, most sustained release, whereas brand B and brand C showed faster release kinetics, correlating with the absence of microspheres. Conclusions: Overall, the test product gels demonstrate Q3 equivalence to the RLD and outperform Indian market products in structural and release characteristics, suggesting their suitability for bioequivalence and regulatory alignments.